Interaction of Internal and External Organizations in Encouraging Community Innovation - Prasetyo, Andjar; Putri Harwijayanti, Bekti; Ikhwan, Muhammad Nur; Lukluil Maknun, Moch; Fahlevi, Mochammad (Frontiers in Psychology, 2022)
An area generally has a different character from other regions, including the limited resources that exist in the area. Therefore, it is necessary to strive to encourage human resources through various interactions, one of the efforts made is the interaction of organizational capacity in the field of innovation. The purpose of this study is to analyze and evaluate the process of organizational interaction in the field of community innovation in Magelang City, Central Java Province, Indonesia. Secondary data sources from the Magelang City Research and Development Agency were 322 innovations from 2004 to 2019, while the primary data came from structured interviews with ten innovators. The findings of the analysis are presented with a qualitative description to evaluate the interaction of innovations in the context of local government organizations. The sampling technique in the study uses accidental sampling. The analysis tool uses participatory exploration that focuses on the government's efforts as an internal organization in encouraging the community as an external organization through the interaction of innovation. The findings of this study are the formation of informal organizations in the community through the interaction of innovations carried out through internal organizational mechanisms. The finding in this study is that the organization's internal interactions in innovation are proven to be beneficial for the community which encourages the growth of community innovation, increases people's income, and contributes to increasing Magelang City's Regional Original Income.